Strategi Pemerintah Indonesia dalam Membatasi Impor Telepon Genggam Tiongkok Berlebih Pasca Kerja Sama ASEAN-China Free Trade Area (ACFTA) Periode 2018-2021 - Ahmad Bagus Maulanasyah; Sindy Yulia Putri; Nurmasari Situmeang (Jurnal Ilmiah Wahana Pendidikan, 2023)
Indonesia suffered losses in the electronics sector due to excessive imports of mobile phone products from China and entered easily through the ASEAN-China Free Trade Area agreement throughout 2018-2021. The government makes efforts internally and externally by implementing the Program for Increasing the Use of Domestic Products (P3DN), implementing efforts to use the Indonesian National Standard (SNI), registration. International Mobile Equipment Identity (IMEI), implementing the Prohibition and Restriction of Goods (LARTAS), and entering into agreements with foreign electronics companies namely Huawei, Lenovo and ZTE Cooperation to improve the quality of Indonesian mobile phones. The government also plays an important role as a forum for foreign companies that want to build their factories and invest in Indonesian electronic products in order to advance Indonesian technology so that they can compete with other electronic products in the free market around the world, both with fellow ASEAN members and with China itself.